Women, Work, and Family: A Sociological Study on Female Income Contribution in Rural Maluku Communities - Heatubun, Ave Maria Stella; Turukay, Martha; Sopamena, Junianita F. (KOMUNITAS: Jurnal Ilmu Sosiologi, 2026)
This study aims to analyze women’s economic contribution to household income and the dynamics of their dual roles within rural communities in Maluku, particularly in Sawai Village. Although men are traditionally recognized as primary breadwinners, socio-economic transformations have encouraged women to engage in productive activities such as farming, trading, tailoring, and public employment, yet their contributions remain socially and statistically undervalued. Using a qualitative approach within the framework of economic sociology and gender studies, this research employs in-depth interviews, participant observation, and social documentation, analyzed thematically through categories of economic contribution, domestic roles, social perception, and gender adaptation. The findings reveal that women in Sawai play a significant role in sustaining household economies, contributing an average of 28.38% to total income, with the highest contribution (42.70%) coming from formal employment. These results indicate a shift in the gendered division of labor, as women become integral to household economic structures despite limited social recognition under prevailing patriarchal norms. The study’s novelty lies in applying a locally grounded economic sociology perspective to postcolonial rural Maluku, integrating quantitative and qualitative insights. Theoretically, it advances discourse on gendered economic participation, while practically offering policy implications for culturally sensitive women’s economic empowerment in Indonesia’s eastern rural contexts.